Joint optimization of trajectory and resource allocation for UAV integrated radar and communication system - Shaoshuai FAN; Yufei WANG; Hui TIAN; Jie Zhang; Jinxin SHI (Tongxin xuebao)
For the flexible and efficient area detection and data transmission tasks, the joint optimization of time resource allocation, power resource allocation and the trajectory for UAV (unmanned aerial vehicle) trajectory for airborne IRCS (integrated radar and communication system) was studied in a TDM (time division multiplexing) manner, in order to maximize the total weighted capacity of the system’s radar detection link and communication transmission link.To solve the non-convex optimization problem, the BCD (block coordinate descent) and the SCP (successive convex programming) techniques were adopted to iteratively optimize the time resource allocation, power resource allocation and UAV trajectory.The simulation results demonstrate that the proposed method can obtain a convergent solution, and can effectively improve the capacity of the system.